(untitled) (European Journal of Child Development, Education and Psychopathology, 2021)
The interest in examining personal constructs such as empathy may be relevant in psychology university students who will dedicate themselves professionally to the care of different groups, such as the elderly. This work analyzes whether empathy can differ according to sociodemographic variables such as age and sex of psychology university students. The sample is made up of 212 participants of different levels of training from Alicante and province. Of them, 64.6% were women and 35.4% were men, with a mean age of 22.34 (SD = 7.02). The instrument used was the Basic Empathy Scale (2006), abbreviated form, made up of 9 items in Likert-type format that analyzes cognitive and affective empathy. For this, an online questionnaire was created, hosted by Google, to which the participants answered voluntarily and anonymously. The results were statistically significant in Psychology students according to gender, age and training course. These data suggest that this ability can develop and evolve according to a multitude of personal variables, as well as contextual factors. These results help to understand the importance of delving into the possible empathy deficiencies of these future professionals and with it, encourage those students with these most deficient potentialities in order to promote their professionalism.